Strategi Pemasaran Digital Dalam Meningkatkan Usaha Kecil Dan Menengah - Suwandi Suwandi; Wardah Sahrani Sibarani; Lola Amalia Sibarani; Syafitri Halawa (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Cyberspace is now no longer only able to connect people with devices, but also people with other people throughout the world. It is hoped that the existence of MSMEs will be able to stimulate the economy amidst the current economic slowdown. The use of digital technology-based marketing concepts (digital marketing) gives hope for MSMEs to develop into economic powerhouses. MSME players collaborate on promotional media and digital-based distribution media to gain maximum profits. Currently, almost all MSME businesses or even restaurants and fast food businesses use digital marketing-based promotional media and distribution media. This research focuses on discussing the role of digital marketing as a marketing strategy for Micro, Small and Medium Enterprises (MSMEs) through the concept of people’s economic empowerment. This strategy is an adaptation step to be able to survive and transform into superior Micro, Small and Medium Enterprises (MSMEs) in the era of the industrial revolution 4.0.